MANAJEMEN SUMBER DAYA MANUSIA DI KANTOR KECAMATAN KANGAYAN - Hamka; Satunggale Kurniawan; Rahman, Muhammad Afifi (PT. Jurnal Center Indonesia Publisher, 2024)
HR (Human Resources) development in sub-district offices refers to efforts to improve the quality, capacity and performance of employees working at the sub-district level. HR development is a strategic process that involves various activities and programs to strengthen the capabilities of individuals, teams and the organization as a whole. The aim is to improve efficiency, effectiveness and services provided to the community. Human resources are one of the most important assets for an organization/company. The role of human resources for organizations/companies is not only seen from the results of work productivity but also seen from the quality of work produced, even further, the superiority of an organization/company is also determined by the superiority of its human competitiveness, not determined by its natural resources. The stronger the knowledge of human resources, the stronger the company's competitiveness. Improving the quality of human resources, and therefore, this paper draws a conclusion, namely